(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Language as a socio-psychological phenomenon always strives for brevity and convenience. It is more convenient and easier for someone to pronounce it correctly than to pronounce it correctly. The use of phonetic and lexical words in the language provides some comfort and fluency. The main element of the work of art is the word and the language in general, and the language is the main factor of the author’s ability to use language tools to raise this work to the level of real art.